Evaluation of frost heave model using measured values for temperature and water intake rate near the freezing front - Takeshi Ishizaki; Satoshi Nishimura (Soils and Foundations)
Many frost heave theories and models have been proposed to explain the frost heave phenomenon. In the present study, systematic frost heave experiments were conducted under various temperature gradients and freezing rates, and the relationships between the water intake rate and the freezing front, freezing rate, temperature gradient in the frozen zone, and temperature of the ice lens growth surface were investigated. The experimental results showed that there is a linear relationship among the water intake rate, freezing rate, and temperature gradient, and that there is also a linear relationship between the water intake rate and the temperature of the ice lens growth surface. Based on these findings, the validity of the existing frost heave models was evaluated. The results of this study revealed that the water intake rate to the freezing front cannot be expressed only by the temperature gradient in the frozen fringe. In addition, a model in which the rate of the water intake into the ice lens is determined by the hydrodynamic resistance of the water flow in the frozen fringe cannot explain the experimental results well. With a kinetic model, in which the water intake rate is determined by the chemical potential difference between the ice lens and the nearby water film, it was found that the calculated results and the actual measurement results corresponded well when the self-diffusion coefficient of the water film near the ice lens was used as a fitting parameter.